Estimation of pergamine coffee moisture using an automated solar dryer, by mathematical models in Jaen-Peru - Quiñones Huatangari, Lenin (2020)
Coffee is a product widely consumed worldwide, because it has a stimulating and energizing power. In addition, the drying process is an essential factor that influences the final quality of the product, in this sense, the objective of this article was to estimate the humidity of parchment coffee by using an automated solar dryer, using mathematical models. The models used were multiple linear regression and nonlinear regression, the same as those determined with the R and Curve Expert Professional software respectively. The data needed to estimate these models, were collected in the field for five days, which consisted of applying the automated solar dryer on the plot of a farmer from the town center of Las Naranjas, Jaén, Cajamarca, Peru whose variety was Catimor. Five models were determined: A multiple linear regression model and four non-linear models with a correlation coefficient  greater than 0.91. However, the model used to describe solar radiation in Greece is the one that best describes the moisture behavior of parchment coffee grade in terms of the drying time in the automated solar dryer using goodness of fit statistics.